Pharmacological and economical aspects of important species of Cordyceps sensu lato: A review: Pharmacological and economically important of Cordyceps - Al-Khayri, Jameel M.; Khan, Tahir (Cellular and Molecular Biology, 2024)
Cordyceps is a well-known endo-parasitic fungus commonly used in traditional Chinese medicine for a long time. The demand for Cordyceps is increasing daily because it is commonly used as a nutritional food, medicine, and supplement owing to its natural source. It is very attractive in almost all countries with no side effects. Most Cordyceps species have been studied in China, Bhutan, India, Japan, South Korea, and Nepal. We have discussed the important contents of Cordyceps, dietary source and nutritional value of Cordyceps, multiple pharmacological properties of four important Cordyceps species, Ophiocordyceps sinensis, Cordyceps militaris, Cordyceps cicadae, and Cordyceps tenuipes, along with the economic status of Cordyceps and its benefits in terms of medicine, supplements, and the cosmetics industry. Owing to the high demand and several benefits of Cordyceps, it offers mysterious economic improvements in developed and underdeveloped countries. Therefore, more attention is required to save the endangered species of Cordyceps to fulfil the medicinal and nutritional demands worldwide.